Isolation and reconstitution of cytochrome P450ox and in vitro reconstitution of the entire biosynthetic pathway of the cyanogenic glucoside dhurrin from sorghum. - Kahn, R A (1997)
A cytochrome P450, designated P450ox, that catalyzes the conversion of (Z)-p-hydroxyphenylacetaldoxime (oxime) to p-hydroxymandelonitrile in the biosynthesis of the cyanogenic glucoside beta-D-glucopyranosyloxy-(S)-p-hydroxymandelonitrile (dhurrin), has been isolated from microsomes prepared from etiolated seedlings of sorghum (Sorghum bicolor L. Moench). P450ox was solubilized using nonionic detergents, and isolated by ion-exchange chromatography, Triton X-114 phase partitioning, and dye-column chromatography. P450ox has an apparent molecular mass of 55 kD, its N-terminal amino acid sequence is -ATTATPQLLGGSVP, and it contains the internal sequence MDRLVADLDRAAA. Reconstitution of P450ox with NADPH-P450 oxidoreductase in micelles of L-alpha-dilauroyl phosphatidylcholine identified P450ox as a multifunctional P450 catalyzing dehydration of (Z)-oxime to p-hydroxyphenylaceto-nitrile (nitrile) and C-hydroxylation of p-hydroxyphenylacetonitrile to nitrile. P450ox is extremely labile compared with the P450s previously isolated from sorghum. When P450ox is reconstituted in the presence of a soluble uridine diphosphate glucose glucosyltransferase, oxime is converted to dhurrin. In vitro reconstitution of the entire dhurrin biosynthetic pathway from tyrosine was accomplished by the insertion of CYP79 (tyrosine N-hydroxylase), P450ox, and NADPH-P450 oxidoreductase in lipid micelles in the presence of uridine diphosphate glucose glucosyltransferase. The catalysis of the conversion of Tyr into nitrile by two multifunctional P450s explains why all intermediates in this pathway except (Z)-oxime are channeled.